2010
DOI: 10.1038/ncb2098
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a co-activator that links growth factor signalling to c-Jun/AP-1 activation

Abstract: The AP-1 transcription factor c-Jun is essential for cellular proliferation in many cell types, but the molecular link between growth factors and c-Jun activation has been enigmatic. In this study we identify a previously uncharacterized RING-domain-containing protein, RACO-1 (RING domain AP-1 co-activator-1), as a c-Jun co-activator that is regulated by growth factor signalling. RACO-1 interacted with c-Jun independently of amino-terminal phosphorylation, and was both necessary and sufficient for c-Jun/AP-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 44 publications
5
60
0
Order By: Relevance
“…Activation of ERK has been considered to be involved in cell proliferation (McCubrey et al, 2007;Abrams et al, 2010); while inhibition of ERK activation with a MEK inhibitor, PD98059, induced apoptosis in a dose-dependent manner in breast cancer cells. The ERK pathway was up-regulated in human cancers, such as colon cancer (Davies et al, 2010), and blockage of the ERK pathway would enhance the induction of apoptosis in cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of ERK has been considered to be involved in cell proliferation (McCubrey et al, 2007;Abrams et al, 2010); while inhibition of ERK activation with a MEK inhibitor, PD98059, induced apoptosis in a dose-dependent manner in breast cancer cells. The ERK pathway was up-regulated in human cancers, such as colon cancer (Davies et al, 2010), and blockage of the ERK pathway would enhance the induction of apoptosis in cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…(Davies et al, 2010). Arginine methylation appeared to counteract RACO-1 degradation, as overexpression of myc-PRMT1 led to a considerable increase in RACO-1 protein levels ( Figure 5A) and half-life as determined by CHX chase ( Figure 5B).…”
Section: Prmt1 Methylates Raco-1mentioning
confidence: 99%
“…We have previously shown that K48-linked autoubiquitylation is counteracted by Ras/MEK1-induced K63-linked ubiquitylation (Davies et al, 2010). Given that arginine methylation can affect the deposition of other posttranslational modifications on the same protein (Hyllus et al, 2007;Yamagata et al, 2008), we thus investigated the impact of arginine methylation on K63-linked ubiquitylation of RACO-1.…”
Section: Prmt1 Methylates Raco-1mentioning
confidence: 99%
See 2 more Smart Citations